Effect of the Initial Shape of Coronal Mass Ejections on 3‐D MHD Simulations and Geoeffectiveness Predictions. Issue 6 (28th June 2018) - Scolini, C.; Verbeke, C.; Poedts, S.; Chané, E.; Pomoell, J.; Zuccarello, F. P.
Abstract: Coronal mass ejections (CMEs) are the major space weather drivers, and an accurate modeling of their onset and propagation up to 1 AU represents a key issue for more reliable space weather forecasts. In this paper we use the newly developed EUropean Heliospheric FORecasting Information Asset (EUHFORIA) heliospheric model to test the effect of different CME shapes on simulation outputs. In particular, we investigate the notion of "spherical" CME shape, with the aim of bringing to the attention of the space weather community the great implications of the CME shape implementation details for simulation results and geoeffectiveness predictions. We take as case study an artificial Earth‐directed CME launched on 6 June 2008, corresponding to a period of quiet solar wind conditions near Earth. We discuss the implementation of the cone model used to inject the CME into the modeled ambient solar wind, running several simulations of the event and investigating the outputs in interplanetary space and at different spacecraft and planetary locations. We apply empirical relations to simulation outputs at L1 to estimate the expected CME geoeffectiveness in terms of the magnetopause stand‐off distance and the induced Kp index. Our analysis shows that talking about spherical CMEs is ambiguous unless one has detailed information on the implementation of the CME shape in the model. All the parameters specifying the CME shape in the model significantly affect simulation results at 1 AU as well as the predicted CME geoeffectiveness, confirming the pivotal role played by the shape implementation details in space weather forecasts. Key Points: The EUHFORIA heliospheric model is used to test the effect of different realizations of a CME spherical shape on simulation outputs Our analysis indicates that the CME shape implementation details significantly affect simulation results and space weather predictions Talking about "spherical" CMEs is ambiguous unless detailed information on the implementation of the CME shape in the model is provided